2020
DOI: 10.1017/s0007114520002688
|View full text |Cite|
|
Sign up to set email alerts
|

Consumption of ultra-processed foods and health status: a systematic review and meta-analysis

Abstract: Increasing evidence suggests that high consumption of ultra-processed foods (UPF) is associated with an increase in non-communicable diseases, overweight and obesity. The present study systematically reviewed all observational studies that investigated the association between UPF consumption and health status. A comprehensive search of MEDLINE, Embase, Scopus, Web of Science and Google Scholar was conducted, and reference lists of included articles were checked. Only cross-sectional and prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
422
1
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(535 citation statements)
references
References 47 publications
11
422
1
24
Order By: Relevance
“…Increase of UPF may have negative long-term effect on health as prior data from longitudinal studies showed that habitual consumption of highly processed foods leads to a higher risk of cardiovascular disease, cancer, diabetes and mortality (12)(13)(14)(15)20).…”
Section: Discussionmentioning
confidence: 99%
“…Increase of UPF may have negative long-term effect on health as prior data from longitudinal studies showed that habitual consumption of highly processed foods leads to a higher risk of cardiovascular disease, cancer, diabetes and mortality (12)(13)(14)(15)20).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence is showing that having a large proportion of ultra-processed foods in the diet is associated with certain adverse health outcomes. 80 -82 Observational studies have shown associations between diets containing high proportions of ultra-processed foods and NCDs including CVD and cancer. An RCT reported a causal relationship between a diet containing a high proportion of ultra-processed foods and obesity.…”
Section: Dietary Pattern Evidence For Defining Healthy Dietsmentioning
confidence: 99%
“…27 This result is consistent with a similar systematic review which reported a significant association between the highest ultra-processed food consumption and increased risk of overweight and obesity in 73,169 adults (odds ratio: 1.39, 95% CI: 1.29, 1.50; p < 0.0001, I 2 ¼ 0%, p ¼ 0.47). 28 This review also reported statistically significant associations between highest ultra-processed food consumption and an increased risk of high waist circumference or abdominal obesity, an increased risk of the metabolic syndrome and reduced highdensity lipoprotein cholesterol levels in adults. 28 Additionally, this review also reported that among the included prospective cohort studies, the highest consumption of ultra-processed foods was significantly associated with an increased risk of all-cause mortality, an increased risk of cardiovascular disease incidence and/or mortality, cerebrovascular disease incidence/ and or mortality, depression, and overweight and obesity in adults.…”
Section: Global Energy Imbalance: a Dietary Perspectivementioning
confidence: 74%
“…28 This review also reported statistically significant associations between highest ultra-processed food consumption and an increased risk of high waist circumference or abdominal obesity, an increased risk of the metabolic syndrome and reduced highdensity lipoprotein cholesterol levels in adults. 28 Additionally, this review also reported that among the included prospective cohort studies, the highest consumption of ultra-processed foods was significantly associated with an increased risk of all-cause mortality, an increased risk of cardiovascular disease incidence and/or mortality, cerebrovascular disease incidence/ and or mortality, depression, and overweight and obesity in adults. 28 The results of these reviews highlight the potential health benefits of limiting consumption of ultra-processed foods in the diet, which may lead to a reduced risk of weight gain, overweight and obesity, and reduced risk of chronic disease development in adults.…”
Section: Global Energy Imbalance: a Dietary Perspectivementioning
confidence: 74%